THE GEOMAGNETIC CONTROL CONCEPT OF THE F2-LAYER PARAMETER LONG-TERM TRENDS - Mikhailov A.V. (My University, 2002)
The geomagnetic control concept relates F2-layer parameter trends with long-term variations of geomagnetic activity and allows one to explain both foF2 and hmF2 trends consistently. Periods with negative and positive trends correspond to the periods of increasing or decreasing geomagnetic activity. The applied method gives the trends which are significant at the 95–99% confidence level for most of local time moments. Daytime foF2 trends show a pronounced dependence on geomagnetic (invariant) latitude with the largest negative (positive) trends for rising (falling) periods of geomagnetic activity at high latitudes and small trends at lower latitudes. No latitudinal dependence was found for the hmF2 trends, which are positive at most of the stations considered for the period of increasing geomagnetic activity. This difference is due to different NmF2 and hmF2 dependencies on main aeronomic parameters. For the period of increasing geomagnetic activity the revealed daytime foF2 and hmF2 trends may be related with neutral composition and temperature perturbations while meridional thermospheric wind at lower and middle latitudes and soft electron precipitation in the auroral zone determine to a great extent the mechanism of the nighttime trends formation. Thus main morphological features of the foF2 and hmF2 trends may be explained in the framework of contemporary F2-layer storm mechanisms, i.e., they have a natural origin rather than an artificial one.